G. E. Moore on Concepts and Judgment [G. E. Moore Sobre Conceptos y Juicio] - Briceno-Dominguez, J (Sociedad Argentina de Analisis Filosofico, 2021)
In "The Nature of Judgment" (1899), G. E. Moore defends the strange thesis according to which "[i]t seems necessary... to regard the world as formed of concepts". Philosophers have offered distinct understandings of this proposal, in particular of what Moorean concepts really are. In this article I discuss and reject three of them: one, according to which Moorean concepts are universals within the framework of a bundle theory of concrete particulars (Nelson, 1962; Baldwin, 1990); a second one, according to which Moorean concepts are particulars within a mereological framework of analysis (Bell, 1999); and a third one, according to which Moorean concepts are a sui generis category, resulting from his alleged rejection of the substance (particular)/attribute (universal) distinction (MacBride, 2018). I end by defending my own understanding, which highlights the openly Platonic stance of the young G. E. Moore. © 2021 Sociedad Argentina de Analisis Filosofico. All rights reserved.
Keywords: Abstract; Concepts; Judgment; Particular; Proposition; Substance; Universal